Customer satisfaction among international tourists towards local service provider at Bandar Hilir, Melaka / Nuramirah Mohd Koyah and Siti Karimah Ibrahim - Mohd Koyah, Nuramirah; Ibrahim, Siti Karimah (Faculty of Business and Management, 2014)
This research is mainly focus on the service quality dimensions that includes tangible, reliability, responsiveness, assurance and empathy that influence tourist satisfaction at Bandar Hilir, Melaka. The objectives of this study are to identify the elements of service quality that gives impact on tourist perception towards service provider and also to define level of satisfaction towards tourists about service provider in Bandar Hilir Melaka. Besides that, in order to determine the most influence elements in service quality that gives satisfaction towards tourists in Bandar Hilir Melaka. From the result of this research will shows that whether the tourists that comes to Bandar Hilir satisfied or not towards the service that provide by service provider and how well the service quality dimensions influence the tourists satisfaction at Bandar Hilir, Melaka. Therefore, this research has been set up and been carried out to test and reveal the answer of this research objectives.